Experience of Managing Ureterovaginal Fistulas following Obstetric and Gynecological Surgeries - Upadhyay, Amit Mani; Kunwar, Ashok; Shrestha, Sanjesh; Pradhan, Hema Kumari; Karki, Aruna; Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Iatrogenic ureteric injuries leading to fistula are rare but devastating complications of obstetric and gynecological surgeries.The aim of the study is to review the demography of ureterovaginal fistula (UVF) and its surgical outcome in the starting phase of fistula surgery. Methods: This is a retrospective review of 15 patients of ureterovaginal fistula who were referred to department of Obstetrics and Gynaecology of Kathmandu Model Hospital from Feb 2014 to Sept 2017. The study reviewed the demography, causes and surgical outcome of ureterovaginal fistula (UVF). Ten patients who had complete blind end at the distal ureter undergone Lich-Gregoir extravesicalur enteroneocystostomy. In other 5 patients, guide wire was successfully negotiated beyond the fistula site, however retrograde double J stenting could be done in only 4 patients. Results: All the patients had distal ureteric injury close to vesicoureteric junction leading to ureterovaginal fistula. Among them, majority were due to post hysterectomy 60% (n=9) followed by obstetrics procedures (caesarean section) 40% (n=6). Fourteen patients (93%) had successful closure of the fistula with complete preservation of renal function till date. Retrograde double J stenting was possible in patients who were referred earlier within two weeks of the onset of injury. Conclusions: In our short review, iatrogenic injury to the distal ureter during Obstetrics/Gynaecologic surgery was found to be the leading cause for the formation of ureterovaginal fistula. Endoscopic management with ureteric stents is still possible if the patients are referred earlier following primary surgery.